Rancang Bangun Aplikasi Sirkulasi Perpustakaan pada SMA Hang Tuah 4 Surabaya - dewantara, Brahmastya Mahardhika; Sudarmaningtyas, Pantjawati; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
Hang Tuah 4 senior high school is an agency engaged in education, located at Jalan Bogowonto 18, Surabaya. As an institution engaged in education, Hang Tuah 4 high school has supporting facilities for teaching and learning activities, namely a library. The problems that exist in the library of SMA Hang Tuah 4 Surabaya, among others. Lack of information about the amount of book information during the borrowing process, difficulties in checking borrower data, and events in information delivery. Meanwhile, in the process, errors occur when checking data. There is accumulation of data in recording the number of visits, because it is done once a week. The operator must adjust the loan data to the level of the fine amount. The above problems are solved by designing a web-based library circulation application. Applications can record loans and visits, library visits, and calculate fines automatically. In addition, this application also features a collection search and report generation. The method used in application development uses the System Development Life Cycle using the Waterfall model. The stages carried out include communication, planning, modeling, and construction. Tests carried out using the black box testing method on 45 test cases, obtained a 100% conformity level. This shows that the circulation of web-based applications runs according to its function.